Total Hip Arthroplasty Following Acetabular Fracture Fixation: A Functional Outcome Study - Banskota, Bibek; Rajbhandari, Ansul; Aryal, Rajendra; Pandey, Nitesh Raj; Banskota, Ashok Kumar (Nepal Orthopaedic Association Journal, 2025)
BACKGROUND Total hip arthroplasty (THA) is the endpoint of failed acetabular fracture surgery. Failure may be attributed to causes related injury causing avascular necrosis (AVN) of the femoral head, inadequate articular restoration leading to post-traumatic arthritis, or rarely massive osteolysis of the femoral head. We present a case series of patients who underwent a THA following acetabular fracture or surgery for the same and report their short-term functional outcomes. METHODS Between November 2013 and June 2023, 12 patients underwent a THA for acetabular fracture, all of whom had undergone surgery. There were 11 males and 1 female with an average age of 43 years. The average follow-up was 26 months. Retrospective data on patient and fracture demography, and details of THA prosthesis used, were retrieved from chart and radiograph review, and prospective functional outcome score was measured using the Harris Hip Score (HHS). RESULTS There were 11 males and 1 female, 7 right hip cases, and 5 left hip cases. THAs averaged 12 months after acetabular fracture surgery. The most common index fractures requiring THA were the posterior wall (4) and posterior wall-column (3). The most common bearing couple was ceramic-on-polyethylene. THA was indicated for painful avascular necrosis of the femoral head in 5 cases, massive osteolysis in 2 cases, and poor reduction leading to secondary arthritis in 4 cases. Post-THA Harris Hip Score (HHS) averaged 86, up from 26 pre-op. CONCLUSION THA following acetabular fracture surgery results in significant improvement in functional score for the patient.